Enclaves of poverty in lodz – (not) own neighbourhoods - Nóżka, Marcjanna (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
Enclaves of poverty are neighbourhoods, spaces of reference and identification, where the everyday life of their inhabitants, who have a specific attitude to these places, takes place. In order to show the enclaves of poverty from the perspective and in the opinions of their inhabitants as (not) their own neighbourhoods, the study refers to the results of research conducted over the years in the enclaves of poverty in Łódź. The aim of the study is, among other things, to discuss the multitude of variables that constitute the specificity of the enclaves, which shape and are at the same time shaped by the excluded neighbourhood. Attention was paid, among others, to the variables determining the emergence, constitution and duration of the enclaves of poverty, the changeable understanding of their borders, varying attitudes towards the immediate neighbourhood, perceived as friendly, hostile, indifferent; also discussed are the diverse attitudes of their inhabitants towards the inhabited space. The collected material reveals the image of enclaves of poverty as ambiguous, socially stigmatised spaces, and at the same time as living environments of particular people by whom they are shared and co-created. The same space in the beliefs and feelings of some people may therefore be familiar and safe, willingly inhabited or visited, while for others it will be alien, hostile, and hence usually avoided, unwillingly visited and explored.